Cardiotoxicity in Children With Acute Ieukemia Treated by Anthracycline; Detected by Cardiac Troponins and Echcocardiography - Yaran Abbas Abdulqader; Mouroge Hashim Al-Ani; Nadine Abdulrazzak Mahmood (Advanced Medical Journal)
Background and objectives:the use of anthracycline antineoplastic agents has conducted to improved pediatric malignancies’ outcomes, yet their use is limited by their potential cardiotoxic effects. Thus, children who have received anthracyclines require cardiac evaluation periodically. The serum levels of cardiac troponins have been shown to be elevated in response to severity of cardiac dysfunction. The aim of our study was to investigate the role of serum levels of cardiac troponin and echocardiography as sensitive markers for anthracycline-induced cardiotoxicity in children with malignancy.